Edukasi Dalam Pemeliharaan Kesehatan Gigi Dan Mulut Pada Murid SDN 60 Kota Banda Aceh - Reca; Nuraskin, Cut Aja; Salfiyadi, Teuku; Rahayu, Eka Sri; Mardiah, Ainun; YUsnaini, Rika (Poltekkes Kemenkes Aceh, 2024)
Dental health education is key instilling good oral hygiene practices and correct tooth brushing techniques in students. A community service initiative SDN 60 Banda Aceh City, aimed at Class V students, significantly enhanced their knowledge on dental and oral health using a descriptive educational approach for all 30 class members, with data analyzed univariate analysis. The intervention, which included dental health education remarkably improved students' dental health awareness. Before intervention, students predominantly lacked dental health knowledge; post-intervention, an impressive 96.7% exhibited good knowledge levels. This improvement underscores dental health education's effectiveness and the necessity of health workers' promotive approaches. Participation in School Health Unit (UKGS) activities, emphasizing the right brushing techniques and habits, is crucial for boosting dental and oral health awareness among youth. This experience highlights critical role of dental health education in enhancing students' overall health and well-being, demonstrating its transformative impact.